Objective quantitative analysis of eosinophils and bronchial epithelial cells in induced sputum by laser scanning cytometry. Issue 2 (1st February 1999) - Woltmann, G; Ward, R J; Symon, F A; Rew, D A; Pavord, I D; Wardlaw, A J
Abstract : BACKGROUND: Sputum induction is an important non-invasive technique for measuring airway inflammation in asthma. Cell numbers are often too low for flow cytometric analysis. Laser scanning cytometry (LSC) is a novel technique that allows objective multicolour fluorescence analysis of cells on a microscope slide. METHODS: LSC was used to determine sputum eosinophil and bronchial epithelial cell counts. We first confirmed that we could measure eosinophil counts accurately in peripheral blood using α-major basic protein (MBP) immunofluorescent staining. Sputum induction was performed according to standard protocols. Sputum samples from eight normal controls and 12 asthmatic patients were analysed by LSC and manual counting by two independent observers. Octospot cytospins were fixed and stained with mouse-α-human-MBP monoclonal antibody or mouse-α-human-cytokeratin antibody and goat-α-mouse Oregon Green conjugated second antibody. RESULTS: Sputum induction provided a mean (SE) of 0.99 (0.2) × 10 6 cells per donor. More than 3000 cells on three cytospins per slide were analysed per cell type. The intraclass correlation coefficient (R) and standard deviation (SD) of differences in eosinophils determined by manual counting and LSC were 0.9 and 2.1, respectively, and for bronchial epithelial cell counts they were 0.7 and 2.0. Selective detection of labelled cells was confirmed visually after relocation. CONCLUSION: Eosinophils and bronchial epithelial cells can be accurately and reproducibly counted in an objective manner. LSC is therefore a potentially powerful new method for immunophenotyping leucocytes and epithelial cells objectively in induced sputum in patients with asthma.